2018
DOI: 10.1016/j.foodcont.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted osmotic dehydration of organic cranberries (Vaccinium oxycoccus): Study on quality parameters evolution during storage

Abstract: a b s t r a c tCranberries are appreciated for their high amount of antioxidants such as flavonoids, anthocyanins, phenolic acids, carotenoids and vitamins. However, due to their sour and tart taste they request to be processed into sweeter dried fruits in order to be acceptable for the consumers. The aim of this work was to analyse the effect of ultrasound assisted osmotic dehydration on mass transfer parameters and on quality characteristics during storage of cranberries. Ultrasound treatment was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…This was evidenced by the increasing colour differences values (∆E* 1 ). Generally, a visible difference between samples is considered for ∆E values above 2 [39], so these colour differences were high enough to be appreciated when over 5% (w/w) FF was included, as the sensory evaluation confirmed. These tones can be attributed to the content of carotenoids and other pigments of FF [40].…”
Section: Rheological Properties Of Dough and Cooked Pastamentioning
confidence: 83%
“…This was evidenced by the increasing colour differences values (∆E* 1 ). Generally, a visible difference between samples is considered for ∆E values above 2 [39], so these colour differences were high enough to be appreciated when over 5% (w/w) FF was included, as the sensory evaluation confirmed. These tones can be attributed to the content of carotenoids and other pigments of FF [40].…”
Section: Rheological Properties Of Dough and Cooked Pastamentioning
confidence: 83%
“…The highest WL after 72 h of OD was noted after combined pretreatment with blanching and triplicate lowering of the pressure (BL_3 × 10 v_s). In turn, Nowacka et al [32] reported that US applied as a pretreatment before OD increases the WL during OD, irrespective of the osmotic solution.…”
Section: Resultsmentioning
confidence: 99%
“…However, a solution with the addition of steviol glycosides was used to reduce sugar content in dehydrated fruits. Due to the fact that steviol glycosides are up to 300 times sweeter than sucrose, the addition of little amount (0.1%) of this sweetener is enough to maintain its sweetness comparable with fruits dehydrated in a standard solution [25,32].…”
Section: Methodsmentioning
confidence: 99%
“…To compare the process kinetics, 50% sucrose solution was used in the experiment. Osmotic dehydration was carried out in the range from 30 to 180 min (the optimal process conditions—time and concentration—were selected for testing based on preliminary experiments in a previous work published by Cichowska et al [10]) at a temperature of 40 °C (atmospheric pressure) in ratio of 1:4 (fruit: solution) [23,24]. The mass of a single sample was 20 g ± 2 g. Afterwards, the samples were removed from the osmotic solution and blotted with absorbent paper to remove osmotic liquid from their surface.…”
Section: Methodsmentioning
confidence: 99%